Nurani teaching methods for recitation of the Qur'an : an analytical study of two madrasahs in Dhaka, Bangladesh - Abedeen, Mohammad Jainul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Bangladesh is the third-largest Muslim majority nation in the world and Islam is the state religion. The Qur'an for Muslims is a source of divine blessing, tranquillity and guidance. But, sadly, it's true that a large number of Bangladeshi Muslims are unable to properly recite the Holy Qur'an. Majority of Muslims in Bangladesh, both child and adult learn the Qur'an using the Nurani Teaching Method. This research aims to find out whether Nurani Teaching Method was able to improve student's achievement in the recitation of the Holy Qur'an. This writing is intended to discuss the short historical background of Nurani Teaching Method and its founder in Bangladesh and what are the problems and the challenges in the way of improvement from the present context. This study suggests ways and means to make Nurani Teaching Method productive. This research used several methods in order to understand the Nurani Teaching Method of the Qur'an such as the critical analysis, survey, and data analysis. This study consisted of two Madrasahs of Dhaka, Bangladesh which used Nurani Teaching Method for learning the Qur'an recitation. The data-collecting methods has shown questionnaire and Open-Ended Questions. The data were analysed through Quantitative methods using the statistical package for social science (SPSS) version 21.0 for Windows. The result of the research has shown that learning the Qur'an through Nurani Teaching Method can improve the students' Qur'an recitation skill. However, the Nurani Teaching Method needs to improve with its overall system. In addition, learning recitation of the Qur'an through Nurani Teaching Method also increased the student's motivation in writing Arabic and learning Islamic fundamental knowledge.